2009
DOI: 10.1123/apaq.26.2.102
|View full text |Cite
|
Sign up to set email alerts
|

It’s Okay to Be a Quad: Wheelchair Rugby Players’ Sense of Community

Abstract: This study explored the social experience of wheelchair rugby from the perspective of the players. Eleven national level rugby players (10 males, 1 female with a mean age of 33 years) shared their experiences through the phenomenological methods of semistructured focus group interviews and artifacts. Three themes emerged from the thematic analysis (a) it’s okay to be a quad, (b) don’t tell us we can’t, and (c) the power of wheelchair rugby. The athletes identified with a shared sense of community and the membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
0
34
0
12
Order By: Relevance
“…These findings thus suggest that sport may serve as an effective vehicle to enhance youth's sense of self-worth. This may be particularly important for youth with disabilities as the construction of positive selfidentity has been shown to help combat isolation and stigma (Goodwin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These findings thus suggest that sport may serve as an effective vehicle to enhance youth's sense of self-worth. This may be particularly important for youth with disabilities as the construction of positive selfidentity has been shown to help combat isolation and stigma (Goodwin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Participation in team sports seems to facilitate a sense of community experience, as Goodwin et al (2009) found that wheelchair rugby players expressed various aspects concerning their sense of community, and that it was of great value to be in a community with people with common interests. The fact that all of them were in a wheelchair provided a shared understanding of their disability, their camaraderie both on and off the court and a bond that made it okay to be a quad, both for themselves and for their immediate families.…”
Section: Being Part Of a Communitymentioning
confidence: 95%
“…Themes such as empowerment (Hutzler 1990;Hutzler and Bar-Eli 1993), meaning (Ashton-Shaeffer et al 2001, Gaskin, Andersen, andMorris 2009), self-perception (Blinde and McClung 1997;Huang and Brittain 2006), well-being (Campbell and Jones 1994), quality of life (Giacobbi et al 2008), social competence (Goodwin et al 2009), perception of bodily competence (Kasser 2009;Page, O'Connor, and Peterson 2001) and community integration (Hanson, Nabavi, and Yuen 2001) have all been the focus of these studies. If and how these experiences and competencies exert an impact on participation in other contexts of daily life are rarely articulated.…”
Section: Physical Activity As Social Practicementioning
confidence: 98%
See 1 more Smart Citation
“…O termo "esporte adaptado" designa possibilidades de práticas criadas ou modificadas para suprir as necessidades das pessoas com deficiência de modo a adaptar as regras, os fundamentos e sua estrutura (WINNICK, 2004;MAUERBERG-DECASTRO, 2005;WINNICK, 2011;SILVA et al, 2013). E, a expressão "esporte paraolímpico" é uma representação dos esportes adaptados, porém refere-se ao alto rendimento, ou seja, modalidades esportivas que integram o programa dos Jogos Paralímpicos (GOODWIN et al, 2009;GUTIERREZ;ALMEIDA, 2012;SILVA et al, 2013;BORGMANN;ALMEIDA, 2015).…”
Section: Introductionunclassified